Characteristics of cardiac rehabilitation programs in Latin America and the Caribbean, and estimation of capacity and needs in the region. (25th November 2020) - Chacin, A; Grace, S.L; Anchique-Santos, C; Supervia, M; Turk-Adawi, K; Britto, R; Scantlebury, D; Araya-Ramirez, F; Gonzalez, G; Burdiat, G; Salmon, R; Mamataz, T; et al.
Abstract: Background: Cardiac rehabilitation (CR) is an established model of cardiovascular (CV) prevention that has proven benefits. Availability, characteristics and need of CR programs in Latin-American and Caribbean (LAC) countries remains poorly characterized. This study aims to establish the availability, capacity, density and aspects of CR delivery in LAC. Methods: A cross-sectional survey was administered to CR programs in 24 LAC. Local CV organizations and societies identified CR programs. Characteristics of individual CR program were reviewed including: funding sources, core components, healthcare providers, and dose (number of sessions per weeks X total number of weeks) of CR. National CR capacity (median number of patients a program could serve per year X number of programs per country), density (Ischemic Heart Disease [IHD] incidence per year/ national capacity), need (IHD incidence per year- national capacity) and occupancy (median number patients program served per year/national capacity) were computed based on survey responses. Results: At least one CR program was identified per LAC country (total 255 programs across 24 countries). Data was collected in 20 of the 24 countries. Responses were received from 139/255 programs (median program response rate=55%; Table 1). Over 50% (n=73) of programs were funded by multiple sources (government, hospital/clinic, private health insurance); Self-payment was reported by 63% programs, in which 24 (33.8%) patients paid over 50% of the cost. Guideline-indicated conditions were accepted in 77% or more programs. Physiotherapists (n=106, 76.3%), cardiologists (n=105, 75.5%) and dietitians (n=79, 56.8%) were the most common healthcare providers on CR teams. Regionally, programs offered 9 (IQR = 8–10) core components (patient education, exercise prescription and initial assessment delivered by nearly all programs). Median CR was 36 (IQR = 24–56) sessions/patient. Twenty-seven (20.9%) programs offered alternative CR models (e.g., home or community-based and hybrid models). Median national capacity was 500 CR spots/country (IQR= 200–2300). Regional density was 1 CR spot per 24 incident IHD patients per year. Greatest need in absolute terms for CR was observed in Brazil, Dominican Republic and Mexico (all with >150, 000 spots needed per year to manage incident IHD patients; Table 1). Occupancy ranged from over 100% in Colombia to 15% in Chile (median=60%, IQR = 32%–81%), Table 1. Conclusion: In LAC countries, there is very limited capacity to meet the need for CR. Nature of CR services varied regionally. Funding Acknowledgement: Type of funding source: None